2004
DOI: 10.1002/polb.20022
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous rheology in a nanostructured diblock copolymer/hydrocarbon system and its kinetic origin

Abstract: Nanostructured squalane solutions (5-20 wt %) of a diblock copolymer, poly(styrene-b-hydrogenated isoprene), were prepared by a cosolvent-casting method. The as-cast solutions behaved as viscous liquids with terminal flow behavior at room temperature. Upon heating, the solutions gelled, and they did not return to their starting liquidlike state upon cooling. Small-angle X-ray scattering (SAXS) revealed a random array of spherical micelles in the as-cast solutions, which were hypothesized to be in a nonequilibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Many previous studies [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] of the ordering kinetics of block copolymers have confirmed the nucleation and growth mechanism. For example, experimental observations by Rosedale and Bates 5 and Floudas et al 8,12,13 revealed the relationship ln t 0.5 ∝ (T ODT -T) -n , with n varying between 1 and 2 for several block copolymer melts subjected to a shallow quench.…”
Section: Introductionmentioning
confidence: 90%
“…Many previous studies [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] of the ordering kinetics of block copolymers have confirmed the nucleation and growth mechanism. For example, experimental observations by Rosedale and Bates 5 and Floudas et al 8,12,13 revealed the relationship ln t 0.5 ∝ (T ODT -T) -n , with n varying between 1 and 2 for several block copolymer melts subjected to a shallow quench.…”
Section: Introductionmentioning
confidence: 90%
“…[15][16][17][18][19] Liu et al reported an irreversible viscosity increase with temperature in a diblock copolymer/squalane system. 20,21 Dynamic birefringence measurements, being birefringence measurements under oscillatory deformation, are a useful technique to investigate the molecular origin of stress and molecular dynamics of polymers. This is because the strain-induced birefringence, Dn, of polymeric materials has a strong relationship with the stress s. For example, for rubbery materials, the stressoptical rule (SOR) holds well.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al reported an irreversible viscosity increase with temperature in a diblock copolymer/squalane system. 20,21 In this paper, we investigate the dynamic birefringence and viscoelasticity of diblock copolymer micellar solutions in a less selective solvent and clarify the relaxation modes of such a micellar system in detail. The shear modulus of this system varies slowly with time after temperature quench and shows the transition of viscous to plastic response.…”
Section: Introductionmentioning
confidence: 99%